Fiber-optic catheter for cellular resolution imaging - Cui, Dongyao (2017)
Patients with cystic fibrosis, primary ciliary dyskinesia and chronic obstructive lung disease suffer from airway narrowing and lung infection, leading to morbidity and mortality. Mucociliary clearance (MCC) is a critical self-defense mechanism that prevents respiratory system infection. Impairment of MCC is associated with alterations in the phenotype of epithelial ciliated, mucous, basal cells, etc. How- ever, further understanding of disease pathogenesis and corresponding development for disease diagnosis therapeutics are hindered by lack of an imaging tool for in vivo visualization of these altered phenotype of ciliary function and MCC in real time. Currently available imaging tools cannot provide comprehensive parameters of interest, periciliary liquid (PCL), airway surface liquid (ASL) depth, ciliary beat frequency (CBF) and mucociliary clearance transport (MCT) simultaneously. μOCT has been known as the highest resolution OCT technique available to date and validated as a powerful tool to evaluation MCC and ciliary function. The unprecedented resolution enables quantitative assessment of all parameters of in- terests at the same time within one imaging session. Several major developments were included in this dissertation to translate μOCT towards clinical applications and advance μOCT to higher resolution and better image quality. Four main topics were covered: 1. Visualization of cilia regeneration after injury. 2. Endoscopic μOCT fiber catheter design and prototype toward in vivo clinical applications. 3. Dual spectrometer for in vivo imaging of blood flow. 4. Multifiber μOCT catheter for speckle reduction. We first studied cilia in vivo regeneration with μOCT for a better understanding of the recovery process after certain diseases/accidents. We visualized adult mice tracheas up to 52 days after sulfur dioxide injury and quantified epithelial thickness, cilia coverage, length, beat frequency, coordination, and cilia-generated flow. We observed that regeneration of ciliated cells and cilia completed in 6 days but cilia gradually aligned and functioned in a coordinated way both on individual level and as a group for liquid transport. The later process takes longer. Notably, an overshoot in CBF was observed at the early stage when cilia just fully regenerated. It could be a sign of lag in cilia coordination at the early stage of regeneration. This study was described in Chapter 2. As the previous study was also limited to excised tissues, Chapter 3 presents a novel high-resolution endoscopic μOCT catheter, pushing the clinical feasibility of μOCT a big step forward. The μOCT catheter herein was designed and fabricated to perform longitudinal scanning in vivo in human airways. The outer diameter of 2.4 mm and flexibility allowed it to be inserted into the instrument channel of a standard bronchoscope. Under the real-time video guidance of the bronchoscope, the endoscopic fiber-optics catheter could reach the regions of interest up to sec- ondary bronchi and conduct high resolution, real time imaging of the functional microanatomy of the airway epithelium, including ciliary beat frequency and mu- cociliary transport rates, etc. We demonstrated the feasibility of the catheter using mouse trachea ex vivo and swine trachea in vivo. The next two chapters are dedicated to improve spatial resolution and image quality of μOCT based on benchtop systems. Chapter 4 presents a dual spectrometer μOCT system for extended spectrum band- width detection in order to achieve 1-μm axial resolution. The dual spectrometer design makes it possible to improve axial resolution using NIR radiation and gain improved penetration by use of longer center wavelength. The dual spectrometer utilized two line scan cameras of distinct detection wavelength ranges. The two spectral ranges were combined into a supercontinuum with extended full-width- half-maximum of 345 nm and thus the axial resolution in aqueous environment was 0.93 μm (n = 1.37). In vivo experiment showed blood flow in zebrafish larvae tail vein. Not only individual red blood cell was observed but also endothelial cells lining along the luminal surface of the blood vessel wall. Although at 1 μm resolution μOCT has enough resolving power to identity sub- cellular of biological tissue, some important microstructures was masked behind speckles. With the objective to improve imaging quality at high resolution, a mul- tifiber μOCT catheter was designed to reduce speckle, as described in Chapter 5. The key element in this design was a multi-facet fiber array which actively deliv- ered three light beams onto imaging sample and picked up back-scattered signal at different angles. Simultaneous multichannel spectrometer was employed to detect signals from different channels. Speckle reduction was realized by compounding signals from all channels. Rat esophagus imaging using this setup demonstrated an improved signal-to-noise ratio, contrast-to-noise ration and equivalent number of looks. The epithelium was better delineated from the overlying mucus and lamina propria beneath the basement membrane.